Horner syndrome following endoscopic thyroid surgery (ETS): a report of two cases and literature review - Xie, Tian-Hao; Fu, Yan; Jin, Xiao-Shi; Ha, Si-Ning; Ren, Xiang-Xiang; Sun, Xin-Li; Niu, Zheng (Frontiers in Medicine, 2025)
Horner syndrome (HS), a rare complication of endoscopic thyroid surgery (ETS), manifests as ptosis, miosis, and anhidrosis resulting from oculosympathetic pathway disruption. This study explores HS etiology through two case reports and literature analysis. Case 1 involved a 43-year-old female who underwent unilateral thyroidectomy via a bilateral areolar approach for a thyroid oncocytic adenoma. On postoperative day 1, ptosis and miosis were observed, and the patient was diagnosed with HS. Despite initial glucocorticoid and neurotrophic therapy, symptoms resolved spontaneously by 6 months. Case 2 involved a 36-year-old female with papillary thyroid carcinoma treated via ETS with central lymph node dissection. Transient ptosis and miosis occurred postoperatively and resolved completely after a 6-day course of steroid treatment. Both cases highlighted HS as a complication linked to intraoperative cervical sympathetic chain (CSC) injury, likely due to retractor-induced compression, thermal damage from energy devices, or anatomical variations. A literature review identified only nine prior ETS-related HS cases, emphasizing its rarity (incidence: 0.03%–0.48%). Mechanisms include CSC compression caused by hematoma, edema, or inflammation in confined surgical spaces, with most symptoms resolving as these subside. Differential diagnosis requires excluding intracranial, spinal, or vascular pathologies. Pharmacologic tests utilizing drugs such as Apraclonidine, Cocaine, and Hydroxyamphetamine aid in the diagnosis of HS, while short-term use of steroids and neurotrophins may expedite recovery. Persistent HS beyond 1 year diminishes the likelihood of recovery, necessitating surgical correction for ptosis. ETS, favored for cosmetic outcomes, demands meticulous CSC preservation during dissection, particularly near the superior cervical ganglion. Preoperative patient counseling about HS risk is crucial. This study underscores HS as non-life-threatening yet distressing complication, advocating for refined surgical techniques and heightened anatomical awareness to avoid CSC injury during ETS.